Medication adherence in patients with heart failure: a pilot observational study in outpatient practice - V. N. Larina; K. A. Zamyatin; Ch. G. Gudiev (Российский кардиологический журнал, 2024)
Aim. To assess clinical characteristics and medication adherence in patients with heart failure (HF) with different left ventricle ejection fractions (LVEF).Material and methods. The study involved 65 outpatients aged ≥60 years with a verified diagnosis of HF. A standard physical examination, laboratory and echocardiographic studies were performed. Adherence to treatment was assessed using the National Society of Evidence-B ased Pharmacotherapy Adherence Scale. A patient was considered to have complete adherence with a score of 0, incomplete adherence — ≥1.Results. Preserved LVEF (≥50%) was present in 33 (50,8%) patients (mean age, 76,2±6,6 years). Mildly reduced and reduced LVEF (<50%) was recorded in 32 (49,2%) patients aged 69,8±7,7 years. Regardless of the LVEF, all patients (100%) had two or more chronic diseases, while 45,5% of patients with LVEF ≥50% and 53,1% of patients with LVEF <50% took six or more medications. Most patients took beta-blockers (78,8% in the group with LVEF ≥50%; 87,5% in the group with LVEF <50%), while in isolated cases — angiotensin receptor- neprilysin inhibitors (3% of patients with preserved LVEF; 6,3% — with reduced and moderately reduced LVEF). At the same time, no patient with HF took quadruple therapy. Full adherence to treatment was found in 87,5% of patients in the group with LVEF <50% and in 57,6% in the group with LVEF ≥50%, p=0,007. As the leading reason for noncomplete adherence to treatment, most patients (61,1%) indicated forgetfulness.Conclusion. Complete adherence rate in outpatients with HF with preserved EF is lower than in patients with reduced and mildly reduced EF. Regardless of LVEF, patients with HF require measures to improve medication adherence